Making night-time pedestrians safer using innovative clothing designs. (April 2023) - Black, Alex A.; Brough, Dean; King, Mark; King, Neil; Bentley, Laura A.; Fylan, Fiona; Wood, Joanne M.
Highlights: Poor pedestrian conspicuity increases the risk of collisions with vehicles at night. Biological motion or 'biomotion' configurations increase nighttime pedestrian conspicuity. Biomotion configurations provided longer recognition distances than all other designs. Appealing biomotion designs should be developed for recreational walker and runners. Abstract: Night-time pedestrians, including recreational walkers and runners, remain at significant risk of being killed or seriously injured, because drivers often fail to see them in time to avoid a collision. Clothing incorporating retro-reflective markers on the moveable joints creates a visual perception of biological motion or "biomotion" which has been shown to improve night-time pedestrian conspicuity. This study investigated whether clothing with markings in the biomotion configuration retains its conspicuity if adapted to include thinner or patterned retro-reflective strips making it more acceptable to wear for recreational pedestrians. In a night-time closed road study, the relative conspicuity of pedestrians to 14 young drivers with normal vision (mean age 24.3 ± 3.1 years) was assessed for pedestrians wearing different thicknesses and patterns of biomotion strips and compared with typical clothing worn by night-time pedestrians, including commercially available sports clothing with retro-reflective elements, a fluorescent yellow top, and black clothing. Results showed that all the biomotion configurations resulted in significantly longer recognition distances: around 2 times longer than the sports clothing, 2.5 times longer than the fluorescent top and 4 times longer than the black clothing. Similar trends were found for the distance at which drivers correctly identified pedestrian orientation (towards or sideways to the vehicle), with significantly longer distances for all the biomotion configurations, when compared to the sports, fluorescent top and black clothing. These findings highlight the effectiveness of biomotion clothing, even when using retro-reflective strips as thin as 0.75 cm and have implications for clothing designs for recreational walkers and runners to enhance their night-time safety.